Novel Trypanocidal Inhibitors that Block Glycosome Biogenesis by Targeting PEX3–PEX19 Interaction - Li, Mengqiao; Gaussmann, Stefan; Tippler, Bettina; Ott, Julia; Popowicz, Grzegorz M; Schliebs, Wolfgang; Sattler, Michael; Erdmann, Ralf; Kalel, Vishal C (Frontiers in Cell and Developmental Biology, 2021)
Human pathogenic trypanosomatid parasites harbor unique form of peroxisomes termed glycosomes that are essential for parasite viability. We and others previously identified and characterized the essential Trypanosoma brucei orthologue TbPEX3, which is the membrane-docking factor for the cytosolic receptor PEX19 bound to the glycosomal membrane proteins. Knockdown of TbPEX3 expression leads to mislocalization of glycosomal membrane and matrix proteins, and subsequent cell death. As an early step in glycosome biogenesis, the PEX3-PEX19 interaction is an attractive drug target. We established a high-throughput assay for TbPEX3-TbPEX19 interaction and screened a compound library for small molecule inhibitors. Hits from the screen were further validated using an in vitro ELISA assay. We identified three compounds, which exhibit significant trypanocidal activity but show no apparent toxicity to human cells. Furthermore, we show that these compounds lead to mislocalization of glycosomal proteins which is toxic to the trypanosomes. Moreover, NMR based experiments indicate that the inhibitors bind to PEX3. The inhibitors interfering with glycosomal biogenesis by targeting the TbPEX3-TbPEX19 interaction serve as starting points for further optimization and anti-trypanosomal drug development.